2017
DOI: 10.1021/acsbiomaterials.7b00384
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun Decellularized Lung Matrix Scaffold for Airway Smooth Muscle Culture

Abstract: Chronic respiratory disease affects many people worldwide with little known about the intricate mechanisms driving the pathology, making it difficult to develop novel therapies. Improving the understanding of airway smooth muscle and extracellular matrix (ECM) interactions is key to developing treatments for this leading cause of death. With currently no relevant or controllable in vivo or in vitro models to investigate cell–ECM interactions in the small airways, the development of a biomimetic in vitro model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(33 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…Previous studies with electrospinning dECM have relied on blending with carrier polymers. [27][28][29][30][31][32] We have identified key steps that are crucial for the successful formation of stable, electrospun dECM scaffolds. By homogenizing the dECM into a uniform slurry, any remaining connective tissue could be effectively removed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies with electrospinning dECM have relied on blending with carrier polymers. [27][28][29][30][31][32] We have identified key steps that are crucial for the successful formation of stable, electrospun dECM scaffolds. By homogenizing the dECM into a uniform slurry, any remaining connective tissue could be effectively removed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have reported dECM blended with synthetic polymers to create hybrid scaffolds with enhanced biochemical properties compared with traditional synthetic materials. [27][28][29][30][31][32] However, dECM alone has been shown to be difficult to electrospin and produce stable scaffolds for analysis. To our knowledge, there are no current studies in the literature of successful electrospinning of muscle dECM without a carrier polymer.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been shown that decellularized extracellular matrix (dECM) containing essential proteins for cell attachment and proliferation, could be a good candidate to improve the biocompatibility of copolymers . In a recent study, hybrid electrospun scaffold of poly‐L‐lactic acid and dECM (derived from pig lung) for in vitro ASM model showed that dECM improved physical characteristics (e.g., wettability) …”
Section: Alveolar‐capillary Basement Membrane For Ali Cell Culturesmentioning
confidence: 99%
“…[38][39][40][41] These scaffolds have shown superior mechanical properties and maintenance of bioactivity in various tissue engineering applications. [42][43][44] Different approaches have been applied to bone tissue engineering applications. Gibson and co-workers incorporated decellularized ECM nanoparticles from bone into a biosynthetic nanofiber composite scaffold 45 while Jeon and colleagues have cultured pre-osteoblasts on electrospun PCL scaffolds and decellularized it to obtain decellularized cell-derived ECM scaffolds.…”
Section: Introductionmentioning
confidence: 99%